Ion acoustic wave in relativistic magnetized quantum plasma with positive ions, negative ions, electrons and stationary dust particles - Sarker, Md. Nasim (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Applied Physics and Electronics, 2022.